Adapting the visuo-haptic perception through muscle coactivation - Gerolamo Carboni (Nature Portfolio, 2021)
Abstract While the nervous system can coordinate muscles’ activation to shape the mechanical interaction with the environment, it is unclear if and how the arm’s coactivation influences visuo-haptic perception and motion planning. Here we show that the nervous system can voluntarily coactivate muscles to improve the quality of the haptic percept. Subjects tracked a randomly moving visual target they were physically coupled to through a virtual elastic band, where the stiffness of the coupling increased with wrist coactivation. Subjects initially relied on vision alone to track the target, but with practice they learned to combine the visual and haptic percepts in a Bayesian manner to improve their tracking performance. This improvement cannot be explained by the stronger mechanical guidance from the elastic band. These results suggest that with practice the nervous system can learn to integrate a novel haptic percept with vision in an optimal fashion.